A Vacuum-Powered Artificial Muscle Designed for Infant Rehabilitation - Mijaíl Jaén Mendoza; Samuel Dutra Gollob; Diego Lavado; Bon Ho Brandon Koo; Segundo Cruz; Ellen T. Roche; Emir A. Vela (Micromachines, 2021)
The majority of soft pneumatic actuators for rehabilitation exercises have been designed for adult users. Specifically, there is a paucity of soft rehabilitative devices designed for infants with upper and lower limb motor disabilities. We present a low-profile vacuum-powered artificial muscle (LP-VPAM) with dimensions suitable for infants. The actuator produced a maximum force of 26 N at vacuum pressures of −40 kPa. When implemented in an experimental model of an infant leg in an antagonistic-agonist configuration to measure resultant knee flexion, the actuator generated knee flexion angles of 43° and 61° in the prone and side-lying position, respectively.